2020
DOI: 10.3389/fmats.2020.00224
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Biological and Mechanical Performances of Sintered Hydroxyapatite by Multiple Ions Doping

Abstract: In the present work, hydroxyapatite (HA) nanoparticles doped with Mg 2+ , Sr 2+ , and Zn 2+ ions are developed by wet neutralization method and then sintered at 1,250 • C to obtain bulk consolidated materials. Physicochemical and microstructural analyses show that the presence of doping ions in the HA structure induced the formation of βTCP as secondary phase, during the sintering process, and we found that this effect is depending on the stability of the various doping ions in the hydroxyapatite lattice itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…S-HA at day 14 induced the up-regulation of ten genes including BMP2, COL2A1, SPP1 and SP7, which play important roles in the ossification process. In agreement, previous studies have reported that sintered hydroxylapatite induced the expression of osteogenic genes, including SPP1, in hASCs [19], while high proliferation and focal adhesion kinase activation were observed in human bone marrow mesenchymal stem cells (BM-MSCs) [20].…”
Section: Discussionsupporting
confidence: 92%
“…S-HA at day 14 induced the up-regulation of ten genes including BMP2, COL2A1, SPP1 and SP7, which play important roles in the ossification process. In agreement, previous studies have reported that sintered hydroxylapatite induced the expression of osteogenic genes, including SPP1, in hASCs [19], while high proliferation and focal adhesion kinase activation were observed in human bone marrow mesenchymal stem cells (BM-MSCs) [20].…”
Section: Discussionsupporting
confidence: 92%
“…Biomaterials provide the biological structure that supports MSC osteogenic differentiation [2,[11][12][13][14][15][16][17][18]. The addition of ions has been proved to enhance the osteogenic potential of scaffolds [19]. Biological macromolecules, such as growth factors [20] and microRNAs (miRNAs) [21], as well as biophysical stimuli [22], can also be associated with scaffolds to increase cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Osteogenesis can also be influenced by external aspects such as mechanical forces and electromagnetic fields [ 96 , 97 ]. MSC osteogenic differentiation is supported by the utilized biomaterials [ 98 , 99 ], but the supplementation with ions enhances the osteogenic scaffold potential [ 100 ]. Cell differentiation can also be enhanced with the aid of microRNAs (miRNAs) [ 101 ], GFs [ 102 ], and biophysical stimuli [ 103 ].…”
Section: Micrornas In Mscs Differentiationmentioning
confidence: 99%